Guided reading strategy and its implementation on grade 2 students in Sekolah Pilar Indonesia - Furqon, Miftahul; Wiedarti, Pangesti (LingTera, 2021)
The research is aimed to investigate teachers' implementation of guided reading strategy on grade 2 students in Sekolah Pilar Indonesia. The objectives of the research are (1) to understand how teachers view guided reading as a teaching strategy to develop students' reading comprehension; (2) to describe guided reading strategy implementation which is intended to support grade 2 students' reading comprehension; and (3) to evaluate the learning outcome of guided reading strategy on grade 2 students' reading comprehension. To gain the objectives, the research applied the qualitative case study method. The research subjects comprised four grade-2 teachers and twenty-seven grade-2 students in Sekolah Pilar Indonesia. The data were collected through teacher surveys, in-depth interviews, class observations, and document collection of students' reading assessment records. This research reveals five findings. First, all grade-2 teachers view guided reading as a strategy that can answer inquiries about how to deal with students' different levels of reading and as a context in which students are able to achieve comprehensive reading behaviours. Second, teachers are prepared to implement a guided reading strategy because the essential elements are administered well. Third, the seven essential elements of the guided reading strategy are effective to teach students reading. Fourth, the characteristics often indicators of teacher-self assessment in implementing guided reading strategy are necessarily managed to create an effective guided reading class. Fifth, the learning outcome related to students' reading comprehension shows a significant result.